Applications for Learning Fruits And Animals Using Android-Based Augmented Reality Technology - Lay, Yoseph Martin; Kaburuan, Emil Robert (Universitas Mercu Buana, 2024)
The use of Augmented Reality (AR) technology in education has become an area of research that has attracted attention in recent years. In the context of learning animals and fruits, AR has great potential to increase students' interest and understanding through interesting interactive experiences. By using Unity 3D as a development platform and Vuforia as an AR toolkit, this application is equipped with features such as object detection, visualization of fruits and animals in 3D, as well as additional information about names, descriptions, and additional information about characteristics and characteristics of each object. This study aims to develop a fruits and animals learning application using Android-based Augmented Reality (AR) technology. This application takes advantage of AR capabilities on Android devices to visualize fruits and animals in three dimensions (3D) in the real world.